Study of aerosol optical properties during long-range transport of biomass burning from Canada to Central Europe in July 2013. (November 2016) - Markowicz, K.M.; Chilinski, M.T.; Lisok, J.; Zawadzka, O.; Stachlewska, I.S.; Janicka, L.; Rozwadowska, A.; Makuch, P.; Pakszys, P.; Zielinski, T.; Petelski, T.; Posyniak, M.; et al.
Abstract: The subject of this study is to use in-situ measurements, passive and active remote sensing observations, as well as numerical simulations to describe the temporal variability of aerosol single-scattering properties such as aerosol optical depth (AOD), single scattering albedo (SSA), and aerosol direct shortwave forcing at the Earth׳s surface during the transport of biomass burning (BB) aerosols from Canada to Europe between 2nd and 7th of July 2013. According to the MODIS observations made in the IR spectrum, an area of over 200, 000 km 2 was affected by the BB during the episode. Regarding the AERONET data in Canada, results show a significant variability of AOD within the whole period with a special enhancement between 6th and 9th July, when AOD anomaly led to an increase up to 1.5 (500 nm). Low-values of SSA reported at Yellowknife Aurora and Waskesiu are likely to be due to flaming combustion from closely located source areas. MODIS and CALIPSO observations, as well as numerical simulations of the NAAPS model, show transport of smoke particles over the Northern Atlantic Ocean and further eastward. Indeed, the event was observed at a different times and locations over Europe between 2nd and 14th July. During that period a number of AERONET stations, mainly located close to the Baltic Sea reported AOD at 500 nm of above 1. Compared to Canada the SSA in Europe was higher, indicating particle transformation over the Atlantic Ocean. Lidar observations in the northern Poland showed aerosol layers occurring between PBL height and tropopause with a significant (up to 55%) contribution to the total AOD. However, lidar measurements in Central Poland (Warsaw and Belsk) indicate that aerosols were confined mainly in the middle and lower troposphere. A diurnal mean aerosol direct radiative forcing estimated at the ground level during the event was below −30 W/m 2 with radiative forcing efficiency between −60 and −100 W/m 2 /τ500. The strongest efficiency was found at the Strzyzow station, which was caused by further air mass transformation during its transport over Poland. Highlights: Three different types of biomass burning transport in Europe. Transported to Europe biomass burning was rather small absorbing. Significant aerosol extinction observed in the whole troposphere. Aerosol optical depth anomaly reaches 1.5 in Canada and 1.0 in Europe. Direct aerosol forcing efficiency at surface was from −60 to −90 W/m 2 /τ500 .